The Bodily Expressive Action Stimulus Test (BEAST). Construction and Validation of a Stimulus Basis for Measuring Perception of Whole Body Expression of Emotions - De Gelder, Beatrice; Van den Stock, Jan (Frontiers in Psychology, 2011)
Whole body expressions are among the main visual stimulus categories that are naturally associated with faces and the neuroscientific investigation of how body expressions are processed has entered the research agenda this last decade. Here we describe the stimulus set of whole body expressions termed Bodily Expressive Action Stimulus Test (BEAST), and we provide validation data for use of these materials by the community of emotion researchers. The database was composed by 254 whole body expressions resulting from 46 actors expressing 4 emotions (anger, fear, happiness and sadness). In all pictures the face of the actor was blurred and participants were asked to categorize the emotions expressed in the stimuli in a four alternative forced choice task. The results show that all emotions are well recognized, with sadness being the easiest, followed by fear, whereas happiness was the most difficult. The BEAST appears as a valuable addition to currently available tools for assessing recognition of affective signals. It can be used in explicit recognition tasks as well as in matching tasks and in implicit tasks, combined either with facial expressions, with affective prosody or presented with affective pictures as context in healthy subjects as well as in neurologically atypical populations.